2017
DOI: 10.2147/ott.s140420
|View full text |Cite
|
Sign up to set email alerts
|

Induction chemotherapy followed by intensity-modulated radiotherapy with reduced gross tumor volume delineation for stage T3-4 nasopharyngeal carcinoma

Abstract: PurposeA common problem in stage T3–4 nasopharyngeal carcinoma (NPC) is the narrow gap between the primary tumor and neurological structures, which makes dose optimization difficult. Considering that significant tumor shrinkage may occur during induction chemotherapy (IC), this study explored the efficacy of intensity-modulated radiotherapy (IMRT) using reduced gross tumor volume (GTV) in the treatment of T3–4 NPC.Patients and methodsBetween January 2009 and April 2014, 103 patients with non-metastatic stage T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The use of induction therapy in T4 and N3 is likely to reduce the target volumes for the definitive chemoradiation therapy. Studies have shown that use of induction therapy successfully reduces the target volumes of RT in order to avoid overdosing of critical neurological structures and reduce RT related toxicities 16, 17. For that reason, it is not surprising that we see higher use of induction therapy in these patients with very advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…The use of induction therapy in T4 and N3 is likely to reduce the target volumes for the definitive chemoradiation therapy. Studies have shown that use of induction therapy successfully reduces the target volumes of RT in order to avoid overdosing of critical neurological structures and reduce RT related toxicities 16, 17. For that reason, it is not surprising that we see higher use of induction therapy in these patients with very advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…IMRT is able to escalate the dose to the target while sparing the adjacent critical structures [ 40 , 41 ], and has shown remarkable benefits in local control and relapse-free survival of NPC patients [ 31 , 42 , 43 ]. IMRT/VMAT has been widely applied clinically in the treatment of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al observed no significant differences in 1-, 2-, and 3-year OS, PFS, LRFFS, and DMFS with volume reduction after iCHT ( 29 ). Analogously, the experiences of Zhao et al ( 30 ) and Xue et al ( 31 ) reported good results in terms of disease control with mild toxicities. The dose–volume parameters to take into account in these situations are still to be defined and constitute an interesting field for future research.…”
Section: Discussionmentioning
confidence: 71%